2009
DOI: 10.1089/fpd.2008.0188
|View full text |Cite
|
Sign up to set email alerts
|

Relative Cytotoxicity ofEscherichia coliO157:H7 Isolates from Beef Cattle and Humans

Abstract: Differences and similarities between Escherichia coli O157:H7 isolates from beef cattle and those from sporadic human outbreaks are not fully elucidated. Here, we compared 44 O157:H7 isolates of bovine and human origins (22 isolates of each) to better understand their cytotoxic potential. The Shiga toxin genes stx1, stx2, or both were detected in the 44 isolates, and all elicited Vero cell cytotoxicity. The greatest cytotoxicity was caused by bovine isolates having only stx2 and which represented the majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
(42 reference statements)
2
7
2
Order By: Relevance
“…Also previous studies have observed differences in stx status between human and non-human bacterial strains. However, they observed, in part, different stx patterns than in our study (Fegan and Desmarchelier 2002;Roldgaard et al 2004;Lefebvre et al 2009;Aspan and Eriksson 2010). This is in contrast to the study by Bono et al (2007), which found that stx1 and stx2 status were independent of human or bovine origin.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Also previous studies have observed differences in stx status between human and non-human bacterial strains. However, they observed, in part, different stx patterns than in our study (Fegan and Desmarchelier 2002;Roldgaard et al 2004;Lefebvre et al 2009;Aspan and Eriksson 2010). This is in contrast to the study by Bono et al (2007), which found that stx1 and stx2 status were independent of human or bovine origin.…”
Section: Discussioncontrasting
confidence: 99%
“…However, they observed, in part, different stx patterns than in our study (Fegan and Desmarchelier 2002; Roldgaard et al. 2004; Lefebvre et al. 2009; Aspan and Eriksson 2010).…”
Section: Discussioncontrasting
confidence: 94%
“…Several studies have found an association between the amount of Stx produced and/or the type of stx gene present and the virulence of EHEC O157 strains (3,17,39,43,48). The results presented here suggest that the presence of the stx 2 gene and/or production of higher amounts of Stx may contribute to the increased virulence of CG strains.…”
Section: Discussionsupporting
confidence: 54%
“…Several of these epidemiological studies [41], [42], [43], [45], [46], [47], [48] demonstrated that EHEC O157 carrying stx2a (with or without stx2c ) rather than stx2c were more frequent among clinical isolates, in agreement with the results presented here. Recently, Kawano et al [48] along with others [43], [45], [46] suggested that EHEC O157 carrying stx2c were associated with asymptomatic individuals and mild disease however it is also isolated from patients with severe disease (bloody diarrhea, HC and HUS) as shown by others [23], [40], [41], [44], [47], [49]. Furthermore, Fuller et al recently demonstrated that purified Stx2a is more potent than Stx2c against primary human kidney cell lines and in mouse models [42].…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have evaluated association of stx2a and stx2c content with human virulence [23], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49]. Several of these epidemiological studies [41], [42], [43], [45], [46], [47], [48] demonstrated that EHEC O157 carrying stx2a (with or without stx2c ) rather than stx2c were more frequent among clinical isolates, in agreement with the results presented here.…”
Section: Discussionmentioning
confidence: 99%